PROFESI SALES PROMOTION GIRL (SPG) DI KUTA SELATAN DALAM PERSPEKTIF TUBUH SOSIAL - Shahby, Shafira Rahmarisdewi; Nugroho, Wahyu Budi; Mahadewi, Ni Made Anggita Sastri (JURNAL ILMIAH SOSIOLOGI: SOROT, 2024)
ABSTRACT   This study focuses on the phenomenon of objectification of women who work as Sales Promotion Girl (SPG) in South Kuta, Bali. The purpose of this study is to describe and analyze the objectified SPG profession in South Kuta. This research uses a qualitative approach method with a descriptive- explanatory type. The theory chosen as scalpel in analyzing this research is Mary Douglas’s social body theory. The results of this study reveal that there are moments of objectification felt by SPG starting when they register to become SPG, during training before work, and even while working. SPG has been objectified and made into a job that has the main criteria, namely having an attractive appearance rather than being good at communicating. Then the company, through the event organizer or agency that recruits SPG, will provide work uniforms to SPG. The uniforms provided are standard and according to the company’s wishes. The uniforms given are more often uniforms that are sexy and show the curves of the SPG’s body. SPG have to wear uniforms, whether they like it or not. Apart from that, SPG often feel objectified when working in sexy uniforms. There are potential buyers who stare at SPG's body as if they are objectifying it, which makes SPG feel uncomfortable about this . Keywords: SPG, social body, objectivation.